2021
DOI: 10.3762/bjoc.17.100
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic asymmetric Michael/acyl transfer reaction between α-nitroketones and 4-arylidenepyrrolidine-2,3-diones

Abstract: An organocatalytic asymmetric Michael/acyl transfer reaction between α-nitroketones and 4-arylidenepyrrolidine-2,3-diones is reported. A bifunctional thiourea catalyst was found to be effective for this reaction. With 10 mol % of the catalyst, good results were attained for a variety of 1,5-dihydro-2H-pyrrol-2-ones under mild reaction conditions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In addition, Pan's group has reported an asymmetric organocatalytic Michael/acyl transfer reaction between 4-ylidenepyrrolidine-2,3-diones/4-benzylidenedihydrofuran-2,3-diones 52 and -nitroketones 53, catalysed by bifunctional thiourea catalyst 1J, to afford products 54 in good yields and enantioselectivities (Scheme 15). 60 The reaction scope also expands to an array of 1,5-dihydro-2H-pyrrol-2ones under mild reaction conditions. Scheme 15 Asymmetric Michael reaction between -nitroketones and 4-arylidenepyrrolidine-2,3-diones 60…”
Section: Cluster Account Synlettmentioning
confidence: 98%
“…In addition, Pan's group has reported an asymmetric organocatalytic Michael/acyl transfer reaction between 4-ylidenepyrrolidine-2,3-diones/4-benzylidenedihydrofuran-2,3-diones 52 and -nitroketones 53, catalysed by bifunctional thiourea catalyst 1J, to afford products 54 in good yields and enantioselectivities (Scheme 15). 60 The reaction scope also expands to an array of 1,5-dihydro-2H-pyrrol-2ones under mild reaction conditions. Scheme 15 Asymmetric Michael reaction between -nitroketones and 4-arylidenepyrrolidine-2,3-diones 60…”
Section: Cluster Account Synlettmentioning
confidence: 98%
“…[36][37][38][39][40] Although synthetically easily available and featured in numerous natural products and bioactive molecules, tetramic acids, i. e. pyrrolidine-2,4-dione derivatives, have only once been employed as a substrate in an organocatalyzed transformation. [41] Pyrrolidine-2,3dione [42][43] and pyrrolidine-2,5-dione [44] derivatives have, similarly, seen limited application in organocatalyzed reactions. In continuation of our research on the implementation of pyrrolone derivatives in organocatalyzed asymmetric transformations, [45][46][47][48][49] we herein report the application of N-substituted tetramic acids 3 in the organocatalyzed conjugative addition to nitroalkene acceptors, followed by O-alkylation.…”
Section: Introductionmentioning
confidence: 99%
“…Weinzierl and Waser employed an isothiourea catalyst for esterification-mediated kinetic resolution of paracyclophane derivatives with planar chirality [ 19 ]. Parida and Pan showed that a Michael reaction coupled with an acyl transfer reaction between α-nitroketones and 4-arylidenepyrrolidine-2,3-diones can produce a variety of enantioenriched 1,5-dihydro-2 H -pyrrol-2-ones [ 20 ]. The development of any area is critically dependent on the understanding of underlying features and relationships.…”
mentioning
confidence: 99%